Thermally conductive sheet
Polishing the surface of thermally conductive sheets with anisotropic fillers to a specific curvature improves adhesion and thermal conductivity in the thickness direction, addressing the limitations of existing sheets.
Patent Information
- Application Number
- JP2020549280
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-26
- Filing Date
- 2019-09-25
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2039-09-25
AI Technical Summary
Existing thermally conductive sheets face limitations in increasing thermal conductivity in the thickness direction, and surface roughness from slicing anisotropic fillers like carbon fibers leads to decreased adhesion and increased thermal resistance.
A thermally conductive sheet with anisotropic fillers exposed on the surface is polished to achieve an arithmetic mean curvature of 18000 (1/mm) or less, enhancing surface smoothness and adhesion, thereby improving thermal conductivity in the thickness direction.
The polished surface design increases the contact area with heating elements, reducing thermal resistance and enhancing thermal conductivity in the thickness direction.
Smart Images

Figure 0007618954000003 
Figure 0007618954000004 
Figure 0007618954000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermally conductive sheet, and for example, to a thermally conductive sheet that is disposed between a heat generating body and a heat dissipating body. [Background technology]
[0002] In electronic devices such as computers, automobile parts, and mobile phones, heat sinks and other heat dissipators are commonly used to dissipate heat generated from heat generating bodies such as semiconductor elements and machine parts. It is known that a thermally conductive sheet is disposed between the heat generating body and the heat dissipator in order to increase the efficiency of heat transfer to the heat dissipator. Thermally conductive sheets are generally compressed when placed inside electronic devices, and therefore require high flexibility. Therefore, they are constructed by blending a thermally conductive filler with a highly flexible polymer matrix such as rubber or gel. It is also widely known that thermally conductive sheets have anisotropic fillers such as carbon fibers oriented in the thickness direction to increase thermal conductivity in the thickness direction (see, for example, Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-056315 A [Patent Document 2] JP 2018-014534 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, with the increasing functionality of electrical devices, there is an increasing need for thermally conductive sheets with improved properties, and there is a demand for further increasing the thermal conductivity in the thickness direction. However, as disclosed in Patent Documents 1 and 2, there is a limit to how much the thermal conductivity can be increased by simply orienting the filler in the thickness direction, and further improvements are desired. The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a thermally conductive sheet that can sufficiently improve thermal conductivity in the thickness direction. [Means for solving the problem]
[0005] As a result of intensive research to solve the above problems, the present inventors first tried to increase the contact area between the sheet surface and the contact surface of a heat sink or the like by exposing a part of the anisotropic filler such as carbon fiber in a thermally conductive sheet. However, when the thermally conductive sheet is produced, the sheet is sliced into sheets with a blade. However, simply slicing the sheet into sheets may result in roughening of the sheet surface due to slicing, as well as the cut surfaces of the carbon fibers or the like appearing on the sliced surface. If the sheet surface becomes rough, there is a concern that the adhesion to the contact surface may decrease and the thermal resistance value may increase.
[0006] Therefore, the inventors polished the sliced surfaces to expose the anisotropic filler from the sheet surface, while smoothing the arithmetic mean curve (Spc) of the peaks to a predetermined value or less; specifically, by rounding and smoothing the contact points with the contact surface of a heating element, etc., they succeeded in obtaining a thermally conductive sheet that can increase adhesion to the contact surface, reduce the thermal resistance, and sufficiently improve thermal conductivity in the thickness direction. That is, the present invention is as follows.
[0007] [1] A thermally conductive sheet containing an anisotropic filler in a polymer matrix, at least one of whose surfaces has the anisotropic filler exposed and has an arithmetic mean peak curvature (Spc) of 18,000 (1 / mm) or less. [2] The thermally conductive sheet according to [1], wherein the anisotropic filler is oriented in the thickness direction of the thermally conductive sheet. [3] The thermally conductive sheet according to [1] or [2], wherein at least one of the surfaces has an arithmetic mean height (Sa) of 20 μm or less. [4] The thermally conductive sheet according to any one of [1] to [3], wherein a surface (at least one surface) of the thermally conductive sheet has an interface developed area ratio (Sdr) of 70 or less. [5] The thermally conductive sheet according to any one of [1] to [4], wherein the anisotropic thermally conductive filler is at least one of a fibrous filler and a scaly filler. [6] The thermally conductive sheet according to any one of [1] to [5], having a thickness of 0.1 to 5.0 mm. [7] The thermally conductive sheet according to [6], having a thickness of 0.1 to 0.3 mm. Effect of the Invention
[0008] According to the present invention, it is possible to provide a thermally conductive sheet capable of sufficiently improving thermal conductivity in the thickness direction. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view showing a thermally conductive sheet according to a first embodiment. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing a thermally conductive sheet according to a second embodiment. [Diagram 3] FIG. 2 is a schematic diagram of a thermal resistance measuring device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, the thermally conductive sheet according to an embodiment of the present invention will be described in detail. [First embodiment] Fig. 1 shows a thermally conductive sheet according to one embodiment of the present invention, in which the anisotropic filler is a fibrous material.
[0011] The thermally conductive sheet 10 of this embodiment contains an anisotropic filler 12 in a polymer matrix 14, and the surfaces 10A and 10B have the anisotropic filler 12 exposed and have an arithmetic mean curvature (Spc) of the peaks of 18,000 (1 / mm) or less.
[0012] According to the above configuration, even when the anisotropic filler 12 is exposed from the thermally conductive sheet surface 10A and the sheet surface 10A is uneven, the arithmetic mean curvature (Spc) of the peaks is 18000 (1 / mm) or less, so the sheet surface 10A is smooth, the contact area with the heating element or the like is increased, and the thermal resistance value can be reduced. The arithmetic mean curvature (Spc) of the peaks is preferably 17000 (1 / mm) or less, and more preferably 16000 (1 / mm) or less. The arithmetic mean curvature (Spc) of the peaks is preferably 1000 (1 / mm) or more, and more preferably 5000 (1 / mm) or more.
[0013] The arithmetic mean curvature of the peak (Spc) is a parameter that represents the arithmetic mean of the principal curvatures of the peaks in a defined area, measured in accordance with ISO 25178. A small value indicates that the point of contact with the heating element is rounded. On the other hand, a large value indicates that the point of contact with the heating element is sharp. Although the location of the rounded contact point is not certain, for example, the end or end face of the anisotropic filler exposed on the surface, or the surface consisting of the end of the anisotropic filler and the surface of the polymer matrix, may be the rounded contact point. The arithmetic mean curve of the peaks (Spc) is calculated based on the area of a given measurement (e.g. 1 mm 2 The surface profile of the sample (two-dimensional area) can be calculated by measuring it using a commercially available laser microscope.
[0014] In order to make the arithmetic mean curvature (Spc) of the peaks 18000 (1 / mm) or less, for example, the surface may be polished using abrasive paper with a grain size of #120 to #20000, with the number of polishing times appropriately set according to the grain size. In addition, if necessary, the oriented molded product before being made into the thermal conductive sheet 10 may be adjusted to have an E hardness of about 10 to 80, sliced into sheets, and then polished as described above.
[0015] As shown in Fig. 1, it is preferable that the anisotropic filler 12 is oriented in the thickness direction of the thermally conductive sheet 10 at least inside the thermally conductive sheet 10. According to the above-mentioned configuration, the thermally conductive sheet 10 has high thermal conductivity in the thickness direction, and has a smooth sheet surface and low thermal resistance. To orient the anisotropic filler 12, a treatment such as magnetic field orientation or flow orientation described later may be performed.
[0016] Here, the state in which the anisotropic fillers 12 are oriented in the thickness direction of the thermally conductive sheet 10 refers to a state in which the major axis directions of more than 60% of the anisotropic fillers 12, in terms of number ratio, are oriented within a range of 20° from the thickness direction of the thermally conductive sheet 10. Such an orientation state can be confirmed by observing a cross section of the thermally conductive sheet 10 along the thickness direction with an electron microscope.
[0017] The arithmetic mean height (Sa) of the surface 10A of the thermally conductive sheet 10 is preferably 20 μm or less, and more preferably 1 to 15 μm. When the arithmetic mean height (Sa) is 20 μm or less, the sheet surface has smoothness, and the contact area with the heating element or the like is increased, thereby reducing the thermal resistance value. The arithmetic mean height (Sa) can be measured using a commercially available surface texture measuring device, and specifically, can be measured by the method described in the examples.
[0018] To set the arithmetic mean height (Sa) to 20 μm or less, for example, abrasive paper with a relatively coarse grain size of #120 to #20,000 may be used, and the number of times of grinding may be appropriately set according to the grain size to perform a surface grinding treatment.
[0019] Furthermore, the surface 10A of the thermally conductive sheet 10 preferably has an interface developed area ratio (Sdr) of 70 or less, and more preferably 1 to 60. Even if the thermally conductive filler is exposed from the surface 10A of the thermally conductive sheet 10 and the sheet surface is uneven, by having an interface developed area ratio (Sdr) of 70 or less, the sheet surface is smooth and the contact area with the heating element or the like is increased, thereby reducing the thermal resistance value.
[0020] The developed area ratio (Sdr) of the interface is the ratio of the developed area (surface area) of the defined area to the area (for example, 1 mm 2 ), and a completely flat surface has a developed area ratio Sdr of 0. The developed area ratio (Sdr) of the interface can be measured by the method described in the Examples.
[0021] In addition, to set the developed area ratio (Sdr) of the interface to 70 or less, for example, abrasive paper with a relatively coarse grain size of #120 to #20,000 can be used, and the number of times of polishing can be appropriately set according to the grain size to perform a surface polishing process.
[0022] In this embodiment, the thermally conductive sheet 10 further contains a non-anisotropic filler 16. The thermally conductive sheet 10 has better thermal conductivity by containing the non-anisotropic filler 16. Details of the non-anisotropic filler 16 will be described later.
[0023] The configuration of the thermally conductive sheet according to this embodiment will be described in more detail below. <Polymer matrix> The polymer matrix 14 used in the thermally conductive sheet 10 is a polymer compound such as elastomer or rubber, and is preferably formed by curing a liquid polymer composition (curable polymer composition) consisting of a mixture of a base agent and a curing agent. The curable polymer composition may be, for example, one consisting of an uncrosslinked rubber and a crosslinking agent, or one containing a monomer, a prepolymer, or the like, and a curing agent. The curing reaction may be room temperature curing or heat curing.
[0024] An example of the polymer matrix 14 formed from the curable polymer composition is silicone rubber. In the case of silicone rubber, an addition reaction curing type silicone is preferably used as the polymer matrix (curable polymer composition) 14. More specifically, the curable polymer composition may be one containing an alkenyl group-containing organopolysiloxane and a hydrogen organopolysiloxane.
[0025] In addition to the above, various synthetic rubbers can be used as rubber, and specific examples include acrylic rubber, nitrile rubber, isoprene rubber, urethane rubber, ethylene propylene rubber, styrene-butadiene rubber, butadiene rubber, fluororubber, and butyl rubber. When using these rubbers, the synthetic rubbers may be crosslinked or left uncrosslinked (i.e., uncured) in the thermal conductive sheet. Uncrosslinked rubbers are mainly used for flow orientation. Furthermore, when crosslinking (i.e., curing) is performed, as explained above, the polymer matrix may be a cured curable polymer composition consisting of an uncrosslinked synthetic rubber and a crosslinking agent. As the elastomer, a thermoplastic elastomer such as a polyester-based thermoplastic elastomer or a polyurethane-based thermoplastic elastomer, or a thermosetting elastomer formed by curing a mixed liquid polymer composition consisting of a base agent and a curing agent can be used. For example, a polyurethane-based elastomer formed by curing a polymer composition containing a polymer having a hydroxyl group and an isocyanate can be exemplified. Among the above, it is preferable to use silicone rubber, and in particular addition reaction curing silicone, because the polymer matrix after curing is particularly flexible and has good filling properties for the thermally conductive filler.
[0026] The polymer composition for forming the polymer matrix may be composed of a polymer compound alone, or may be composed of a polymer compound and a plasticizer. The plasticizer is preferably used when synthetic rubber is used, and the inclusion of the plasticizer can increase the flexibility of the polymer matrix when not crosslinked. The content of the polymer matrix, expressed as a filling rate based on volume (volume filling rate), is preferably 20 to 50% by volume, and more preferably 25 to 45% by volume, based on the total amount of the thermally conductive sheet.
[0027] (Additives) In the thermally conductive sheet 10, various additives may be further blended into the polymer matrix 14 within a range that does not impair the function of the thermally conductive sheet 10. Examples of the additives include at least one selected from dispersants, coupling agents, adhesives, flame retardants, antioxidants, colorants, anti-settling agents, etc. Furthermore, when the curable polymer composition is crosslinked or cured as described above, a crosslinking accelerator or curing accelerator that accelerates crosslinking or curing may be blended as an additive.
[0028] <Anisotropic filling material> The anisotropic filler 12 blended into the polymer matrix 14 is a filler having anisotropy in shape and capable of orientation. The anisotropic filler 12 is preferably a thermally conductive filler. As the anisotropic filler 12, a fibrous filler (e.g., a fibrous material such as carbon fiber) or a scaly filler (a scaly material such as graphite, graphene, or boron nitride) is preferable. Even when these anisotropic fillers are exposed on the surface of the thermally conductive sheet 10, causing the sheet surface to have small irregularities, the sheet surface still has good smoothness, and the contact area with the heating element, etc. is increased, thereby further reducing the thermal resistance value.
[0029] The anisotropic filler 12 has a high aspect ratio, specifically, an aspect ratio exceeding 2, and preferably an aspect ratio of 5 or more. By making the aspect ratio larger than 2, it becomes easier to orient the anisotropic filler 12 in the thickness direction, and the thermal conductivity of the thermally conductive sheet 10 can be easily increased. The upper limit of the aspect ratio is not particularly limited, but is 100 for practical purposes. The aspect ratio is the ratio of the long axis length to the short axis length of an anisotropic filler, which in fibrous materials means fiber length / fiber diameter, and in scaly materials means the long axis length / thickness of the scaly materials. From the viewpoint of increasing thermal conductivity, the anisotropic filler is preferably a fibrous material.
[0030] The content of the anisotropic filler 12 in the thermally conductive sheet is preferably 30 to 500 parts by mass, and more preferably 50 to 300 parts by mass, per 100 parts by mass of the polymer matrix. The content of the anisotropic filler 12, expressed as a volume-based filling rate (volume filling rate), is preferably 5 to 60 volume % and more preferably 8 to 45 volume % with respect to the total amount of the thermally conductive sheet. By making the content of the anisotropic filler 12 30 parts by mass or more, it becomes easier to increase thermal conductivity, and by making it 300 parts by mass or less, the viscosity of the mixed composition described below tends to be appropriate, resulting in good orientation of the anisotropic filler 12.
[0031] When the anisotropic filler 12 is a fiber material, the average fiber length is preferably 50 to 500 μm, and more preferably 70 to 350 μm. When the average fiber length is 50 μm or more, the anisotropic filler 12 is in proper contact with each other inside the thermally conductive sheet 10, and a heat transfer path is secured. On the other hand, if the average fiber length is 500 μm or less, the bulk of the anisotropic filler 12 becomes small, and it becomes possible to pack the anisotropic filler 12 highly in the polymer matrix.
[0032] Moreover, the average fiber length of the fiber material is preferably shorter than the thickness of the thermally conductive sheet 10. By making the average fiber length shorter than the thickness, the fiber material is prevented from protruding more than necessary from the surface of the thermally conductive sheet 10. Furthermore, when the anisotropic filler 12 is a scaly material, its average particle size is preferably 10 to 400 μm, more preferably 15 to 200 μm, and particularly preferably 15 to 130 μm. By setting the average particle size to 10 μm or more, the anisotropic filler 12 in the thermally conductive sheet can easily come into contact with each other, ensuring a heat transfer path. On the other hand, by setting the average particle size to 400 μm or less, the bulk of the thermally conductive sheet 10 is reduced, and it becomes possible to highly fill the polymer matrix 14 with the anisotropic filler 12. The average fiber length of the carbon fibers and the average particle size of the scaly material can be calculated, for example, from the fiber length and major axis by observing the anisotropic filler under a microscope. More specifically, for example, the fiber length and major axis of 50 pieces of any anisotropic filler can be measured using an electron microscope or optical microscope, and the average value (arithmetic mean value) can be used as the average fiber length and average particle size.
[0033] The anisotropic filler 12 may be made of a known material having thermal conductivity, but it is preferable that the filler has diamagnetic properties so that it can be oriented in a magnetic field, as described later. Specific examples of the anisotropic filler 12 include carbon-based materials such as carbon fibers or scaly carbon powder, metal materials such as metal fibers, metal oxides, boron nitride, metal nitrides, metal carbides, metal hydroxides, etc. Among these, carbon-based materials are preferred because they have a low specific gravity and good dispersibility in the polymer matrix 14, and graphitized carbon materials with high thermal conductivity are more preferred. Graphitized carbon materials have diamagnetism when the graphite planes are aligned in a specific direction. Boron nitride and the like also have diamagnetism when the crystal planes are aligned in a specific direction.
[0034] Furthermore, the thermal conductivity of the anisotropic filler 12 along the anisotropic direction (i.e., the long axis direction) is generally, but not limited to, 60 W / m·K or more, and preferably 400 W / m·K or more. The upper limit of the thermal conductivity of the anisotropic filler 12 is, but not limited to, 2000 W / m·K or less, for example. The thermal conductivity can be measured by a laser flash method or a method in accordance with ASTM D5470.
[0035] The anisotropic filler 12 may be used alone or in combination of two or more kinds. For example, at least two anisotropic fillers 12 having different average particle diameters or average fiber lengths may be used as the anisotropic filler 12. When anisotropic fillers 12 of different sizes are used, the smaller anisotropic fillers 12 are inserted between the relatively larger anisotropic fillers 12, so that the anisotropic fillers 12 can be densely packed in the polymer matrix and the heat conduction efficiency can be improved.
[0036] Graphitized carbon fiber is preferable as the carbon fiber used as the anisotropic filler 12. Also, flake graphite powder is preferable as the scaly carbon powder. Of these, graphitized carbon fiber is more preferable as the anisotropic filler. Graphitized carbon fiber has graphite crystal planes aligned in the fiber axis direction, and has high thermal conductivity in the fiber axis direction. Therefore, by aligning the fiber axis direction in a specific direction, it is possible to increase the thermal conductivity in a specific direction. Furthermore, flake graphite powder has graphite crystal planes aligned in the in-plane direction of the flake surfaces, and has high thermal conductivity in the in-plane direction. Therefore, by aligning the flake surfaces in a specific direction, it is possible to increase the thermal conductivity in a specific direction. Graphitized carbon fiber and flake graphite powder having a high degree of graphitization are preferred.
[0037] As the graphitized carbon materials such as the graphitized carbon fiber and the flake graphite powder, the following raw materials can be graphitized. For example, condensed polycyclic hydrocarbon compounds such as naphthalene, condensed heterocyclic compounds such as PAN (polyacrylonitrile) and pitch can be mentioned, but it is preferable to use graphitized mesophase pitch, polyimide, and polybenzazole, which have a particularly high degree of graphitization. For example, by using mesophase pitch, the pitch is oriented in the fiber axis direction due to its anisotropy in the spinning process described later, and graphitized carbon fibers having excellent thermal conductivity in the fiber axis direction can be obtained.
[0038] The graphitized carbon fiber may be one obtained by successively subjecting a raw material to spinning, infusibility, and carbonization treatments, pulverizing or cutting to a predetermined particle size, and then graphitizing, or one obtained by pulverizing or cutting after carbonization and then graphitizing. When pulverizing or cutting is performed before graphitization, the newly exposed surface by pulverization is more likely to undergo condensation polymerization and cyclization reactions during the graphitization treatment, and therefore graphitized carbon fiber with a higher degree of graphitization and further improved thermal conductivity can be obtained. On the other hand, when spun carbon fiber is graphitized and then pulverized, the carbon fiber after graphitization is easy to pulverize because it is stiff, and carbon fiber powder with a relatively narrow fiber length distribution can be obtained by pulverization for a short period of time.
[0039] <Non-anisotropic filling material> The non-anisotropic filler 16 is a thermally conductive filler contained in the thermally conductive sheet 10 separately from the anisotropic filler 12, and is a material that imparts thermal conductivity to the thermally conductive sheet 10 together with the anisotropic filler 12. In this embodiment, by filling the sheet with the non-anisotropic filler 16, the increase in viscosity is suppressed and dispersibility is improved before the sheet is hardened. In addition, when the anisotropic filler 12 is mixed with another filler, for example, when the fiber length is large, it is difficult to increase the contact area between the fillers. However, by filling the gap with the non-anisotropic filler 16, a heat transfer path can be formed, and a thermally conductive sheet 10 with high thermal conductivity can be obtained. The non-anisotropic filler 16 is a filler that has substantially no anisotropy in shape, and is a filler that does not orient in a predetermined direction even in an environment in which the anisotropic filler 12 orients in a predetermined direction, such as under the generation of magnetic lines of force or under the action of shear force, as described below.
[0040] The aspect ratio of the non-anisotropic filler 16 is 2 or less, and preferably 1.5 or less. In this embodiment, by including a non-anisotropic filler having such a low aspect ratio, a filler having thermal conductivity is appropriately interposed in the gaps of the anisotropic filler 12, and a thermally conductive sheet 10 having high thermal conductivity is obtained. In addition, by setting the aspect ratio to 2 or less, it is possible to prevent the viscosity of the mixed composition described later from increasing, and to achieve high filling.
[0041] Specific examples of the non-anisotropic filler 16 include metals, metal oxides, metal nitrides, metal hydroxides, carbon materials, oxides, nitrides, carbides, etc. Examples of the shape of the non-anisotropic filler include spherical and amorphous powders. In the non-anisotropic filler 16, examples of metals include aluminum, copper, nickel, etc., examples of metal oxides include aluminum oxide (alumina), magnesium oxide, zinc oxide, etc., and examples of metal nitrides include aluminum nitride, etc. Examples of metal hydroxides include aluminum hydroxide. Furthermore, examples of carbon materials include spherical graphite, etc. Examples of oxides, nitrides, and carbides other than metals include quartz, boron nitride, silicon carbide, etc. Of the above, the non-anisotropic filler 16 is preferably selected from alumina, aluminum, zinc oxide, boron nitride, and aluminum nitride, with aluminum and alumina being particularly preferred from the standpoint of packing properties and thermal conductivity, and alumina being more preferred. The non-anisotropic filler 16 may be one of the above materials, or two or more of them may be used in combination.
[0042] The average particle size of the non-anisotropic filler 16 is preferably 0.1 to 50 μm, more preferably 0.5 to 35 μm, and particularly preferably 1 to 15 μm. By setting the average particle size to 50 μm or less, problems such as disturbance of the orientation of the anisotropic filler 12 are unlikely to occur. Furthermore, by setting the average particle size to 0.1 μm or more, the specific surface area of the non-anisotropic filler 16 does not become larger than necessary, and even if a large amount is blended, the viscosity of the mixed composition is unlikely to increase, making it easy to highly fill the non-anisotropic filler 16. The non-anisotropic filler 16 may be, for example, a non-anisotropic filler 16 having at least two different average particle sizes. The average particle size of the non-anisotropic filler 16 can be measured by observation using an electron microscope or the like. More specifically, for example, the particle sizes of 50 random non-anisotropic fillers can be measured using an electron microscope or optical microscope, and the average (arithmetic mean) of the particle sizes can be used as the average particle size. Alternatively, the average particle size is the volume average particle size of the particle size distribution measured by a laser diffraction scattering method (JIS R1629).
[0043] The content of the non-anisotropic filler 16 is preferably in the range of 200 to 800 parts by mass, and more preferably in the range of 300 to 700 parts by mass, relative to 100 parts by mass of the polymer matrix. The content of the non-anisotropic filler 16, expressed as a filling rate based on volume (volume filling rate), is preferably 30 to 60 volume % and more preferably 40 to 55 volume % with respect to the total amount of the thermally conductive sheet. By setting the amount of the non-anisotropic filler to 200 parts by mass or more, the amount of the non-anisotropic filler 16 present in the gaps between the anisotropic fillers 12 is sufficient, resulting in good thermal conductivity. On the other hand, by setting the amount to 800 parts by mass or less, it is possible to obtain the effect of increasing the thermal conductivity according to the content, and the non-anisotropic filler 16 does not inhibit the thermal conduction by the anisotropic filler 12. Furthermore, by setting the amount within the range of 300 to 700 parts by mass, the thermal conductivity of the thermally conductive sheet 10 is excellent, and the viscosity of the mixed composition is also suitable.
[0044] The ratio of the volume filling rate of the non-anisotropic filler 16 to the volume filling rate of the anisotropic filler is preferably 2 to 5, and more preferably 2 to 3. By setting the volume filling rate ratio within the above range, the non-anisotropic filler 16 is appropriately filled between the anisotropic fillers, and efficient heat transfer paths can be formed, thereby improving the thermal conductivity of the thermally conductive sheet 10.
[0045] <Thermal conductive sheet> The thermal resistance value of the thermal conductive sheet 10 in the thickness direction of the sheet is preferably less than 1° C. / W, more preferably 0.5° C. / W or less, and even more preferably 0.2° C. / W or less. By setting the thermal resistance value to a certain value or less in this way, the thermal conductive sheet 10 can easily transfer heat from a heat generating body to a heat dissipating body. The smaller the thermal resistance value, the better, but it is usually 0.01° C. / W or more. The thermal resistance value can be measured by the method described in the examples.
[0046] The thermal conductivity of the thermally conductive sheet 10 in the thickness direction is, for example, 5 W / m·K or more, preferably 10 W / m·K or more, more preferably 15 W / m·K or more, and even more preferably 18 W / m·K or more. By making the thermal conductivity equal to or greater than these lower limits, the thermal conductivity of the thermally conductive sheet 10 in the thickness direction can be made excellent. There is no particular upper limit, but the thermal conductivity of the thermally conductive sheet 10 in the thickness direction is, for example, 50 W / m·K or less. The thermal conductivity is measured by a method conforming to ASTM D5470-06.
[0047] As described above, the anisotropic filler 12 is exposed on the surface of the thermally conductive sheet 10, making the surface a non-adhesive surface. The non-adhesive surface is not likely to stick to the hands of an operator, and is also easily peeled off when applied with pressure to a contact object such as a heat generating body or a heat dissipating body, which will be described later. In addition, the non-adhesive surface of the thermally conductive sheet 10 allows it to slide when assembled to an electronic device, etc.
[0048] The thickness of the thermally conductive sheet 10 is considered to be in the range of 0.1 to 5.0 mm, but is not necessarily limited to this thickness range. The thickness may be changed as appropriate depending on the shape and application of the electronic device in which the thermally conductive sheet 10 is mounted, but a more preferable thickness is 0.1 to 0.3 mm. With a thickness of 0.1 to 0.3 mm, the thermally conductive sheet becomes a thin film, and is a thermally conductive sheet that easily conducts heat.
[0049] The thermally conductive sheet 10 is used inside electronic devices. Specifically, the thermally conductive sheet is interposed between a heat generating body and a heat sink, and transfers heat generated by the heat generating body to the heat sink by thermal conduction, and dissipates the heat from the heat sink. Here, examples of the heat generating body include various electronic components such as a CPU, a power amplifier, and a power source such as a battery used inside the electronic device. Examples of the heat sink include a heat sink, a heat pipe, a heat pump, and a metal housing of an electronic device. The thermally conductive sheet is used with both surfaces in close contact with the heat generating body and the heat sink, respectively, and compressed.
[0050] <Method of manufacturing thermally conductive sheet> The thermally conductive sheet of the present embodiment can be produced, without particular limitation, by a method including the following steps (A), (B) and (C), for example. Step (A): A step of obtaining an oriented molded body in which anisotropic filler is oriented along one direction that is the thickness direction of a thermally conductive sheet. Step (B): A step of cutting the oriented molded body into a sheet shape to obtain a sheet-shaped molded body. Step (C): A step of polishing the surface of the sheet-shaped body Each step will now be described in more detail.
[0051] [Process (A)] In step (A), an oriented molded body is formed from a mixed composition containing, for example, an anisotropic filler, a non-anisotropic filler, and a polymer composition that is a raw material for a polymer matrix. The mixed composition is preferably cured to form an oriented molded body. More specifically, the oriented molded body can be obtained by a magnetic field orientation method or a flow orientation method, of which the magnetic field orientation method is preferred.
[0052] (Magnetic field orientation method) In the magnetic field orientation method, a mixed composition containing a liquid polymer composition that becomes a polymer matrix after curing, an anisotropic filler, and a non-anisotropic filler is injected into a mold or the like and placed in a magnetic field to orient the anisotropic filler along the magnetic field, and then the polymer composition is cured to obtain an oriented molded product. The oriented molded product is preferably in the form of a block. In addition, a release film may be disposed in the part inside the mold that contacts the mixed composition. For example, a resin film with good releasability or a resin film with one side treated for release with a release agent or the like is used as the release film. By using the release film, the oriented molded body can be easily released from the mold.
[0053] The viscosity of the mixed composition used in the magnetic field orientation manufacturing method is preferably 10 to 300 Pa·s in order to perform magnetic field orientation. By making it 10 Pa·s or more, the anisotropic filler and the non-anisotropic filler are less likely to settle. In addition, by making it 300 Pa·s or less, the fluidity is improved, the anisotropic filler is properly oriented in the magnetic field, and there is no problem such as the orientation taking too long. The viscosity is the viscosity measured at 25°C using a rotational viscometer (Brookfield viscometer DV-E, spindle SC4-14) at a rotational speed of 10 rpm. However, when using an anisotropic or non-anisotropic filler that is difficult to settle, or when combining with an additive such as an anti-settling agent, the viscosity of the mixed composition may be less than 10 Pa·s.
[0054] In the magnetic field orientation manufacturing method, the magnetic field generating source for applying the magnetic field lines includes a superconducting magnet, a permanent magnet, an electromagnet, etc., but a superconducting magnet is preferable because it can generate a magnetic field with a high magnetic flux density. The magnetic field generated from these magnetic field generating sources preferably has a magnetic flux density of 1 to 30 Tesla. When the magnetic flux density is 1 Tesla or more, it becomes possible to easily orient the above-mentioned anisotropic filler made of a carbon material, etc. Also, when it is 30 Tesla or less, it becomes possible to practically manufacture it. The polymer composition may be cured by heating, for example at a temperature of about 50 to 150° C. The heating time is, for example, about 10 minutes to 3 hours.
[0055] (Flow orientation method) In the flow orientation method, a shear force is applied to the mixed composition to produce a preliminary sheet in which the anisotropic filler is oriented in the planar direction, and then multiple sheets of this are stacked to produce a laminated block, which is then used as the oriented molded body. More specifically, in the flow orientation method, first, anisotropic fillers, non-anisotropic fillers, and various additives as necessary are mixed into a polymer composition and stirred to prepare a mixed composition in which the mixed solids are uniformly dispersed. Here, the polymer compound used in the polymer composition may be one that contains a polymer compound that is liquid at room temperature (23°C) or one that contains a polymer compound that is solid at room temperature. The polymer composition may also contain a plasticizer. The mixed composition has a relatively high viscosity so that a shear force is applied when the mixed composition is stretched into a sheet, and specifically, the viscosity of the mixed composition is preferably 3 to 50 Pa s. In order to obtain the above viscosity, the mixed composition is preferably blended with a solvent.
[0056] Next, the mixed composition is flattened and stretched while applying a shear force to form a sheet (preliminary sheet). By applying a shear force, the anisotropic filler can be oriented in the shear direction. As a means for forming the sheet, for example, the mixed composition is applied onto a substrate film by a coating applicator such as a bar coater or a doctor blade, or by extrusion molding or ejection from a nozzle, and then, if necessary, the mixed composition is dried or semi-cured. The thickness of the preliminary sheet is preferably about 50 to 250 μm. In the preliminary sheet, the anisotropic filler is oriented in one direction along the surface direction of the sheet. Next, a plurality of the preliminary sheets are stacked so that they have the same orientation direction, and the mixed composition is cured as necessary by heating, irradiating with ultraviolet rays, etc., while the preliminary sheets are adhered to each other by a hot press or the like to form a laminated block, and the laminated block is used as an oriented molded body.
[0057] [Process (B)] In step (B), the oriented molded product obtained in step (A) is cut by slicing or the like perpendicular to the direction in which the anisotropic filler is oriented to obtain a sheet-like molded product. Slicing may be performed, for example, with a shear blade or a laser. When the sheet-like molded product is cut by slicing or the like, the tips of the anisotropic filler are exposed from the polymer matrix on each surface, which is the cut surface. In addition, at least a part of the exposed anisotropic filler protrudes from each surface. Most of the exposed anisotropic filler does not collapse and is oriented in the thickness direction.
[0058] Here, the oriented molded body preferably has a type E hardness of 10 to 80 as defined by JIS K6253, more preferably 20 to 70. When the E hardness is 10 to 80, when slicing the sheet-shaped molded body, the polymer matrix is more actively cut than the anisotropic filler, making it easier to expose the anisotropic filler. In addition, after slicing to form a thermally conductive sheet, the surface can also be polished to expose the anisotropic filler, since the polymer matrix is more easily worn than the anisotropic filler. Furthermore, if the anisotropic filler is worn in an exposed state, the end of the exposed anisotropic filler is crushed, and an end of a shape bulging toward the surface of the thermally conductive sheet is easily formed, and the contact area with the adherend is increased by the end, so that the thermal conductivity can be further improved.
[0059] [Process (C)] In step (C), the surface of the sheet-like molded body on which the anisotropic filler is exposed is polished. The surface may be polished using, for example, abrasive paper, abrasive film, abrasive cloth, abrasive belt, etc. In this manufacturing method, by polishing the surface of the sheet-like molded body, the anisotropic filler is exposed and the arithmetic mean curvature (Spc) of the peaks is set to 18000 (1 / mm) or less. Therefore, for example, the properties of the abrasive paper are preferably those containing abrasive grains with an average grain size (D50) of 0.1 to 100 μm, more preferably those with an average grain size of 9 to 60 μm. By using abrasive paper with an average grain size of 0.1 μm or more, the anisotropic filler is exposed from the sheet surface, while the arithmetic mean curve (Spc) of the peaks is smoothed to a predetermined value or less, specifically, the contact point with the contacting surface of the heating element or the like is rounded and smoothed. In addition, by using abrasive paper with an average grain size of 100 μm or less, it is possible to prevent scratches that are practically problematic on the surface of the thermal conductive sheet. In addition, for the same reason as above, for example, the grain size of the abrasive grains of the abrasive paper is preferably #120 to 20,000, preferably #300 to 15,000, and more preferably #320 to 4,000. The polishing method can be, for example, polishing by continuously contacting the surface of the thermal conductive sheet with abrasive paper in the same straight line, polishing by going back and forth over a fixed distance, polishing by rotating in the same direction, or polishing by contacting in various directions. The degree of polishing may be determined while observing the surface condition, and in the case of reciprocating polishing, for example, 1 to 300 reciprocating strokes are preferable, 2 to 200 strokes are more preferable, and 3 to 50 strokes are even more preferable. Specifically, it is preferable to polish to such an extent that the protruding length of the anisotropic filler becomes 100 μm or less. It is even more preferable to polish to such an extent that the protruding length becomes 50 μm or less.
[0060] In the above description, the anisotropic filler 12 is exposed on both surfaces 10A, 10B of the thermally conductive sheet 10, and the arithmetic mean curve (Spc) of the peaks is 18000 (1 / mm) or less while the anisotropic filler 12 is exposed on both surfaces 10A, 10B. However, in the present invention, the thermally conductive sheet may have the anisotropic filler 12 exposed on only one of the surfaces 10A, 10B. Therefore, the other of the two surfaces 10A, 10B has an arithmetic mean curvature (Spc) of the peaks of 18000 (1 / mm) or less while the anisotropic filler 12 is exposed, and may have an arithmetic mean curvature (Spc) of the peaks of 18000 (1 / mm) or less even if the anisotropic filler 12 is exposed. In this case, polishing in step (C) is performed on only one of the two surfaces, and the other surface is not polished, or if polished, it is polished under conditions other than those shown in the above step (C). Furthermore, polished objects are very flat even before they are used by being in close contact with a heating element or a heat sink and compressed, and the surface properties after compression are almost unchanged, being only slightly flattened from before compression. In contrast, unpolished objects can be significantly flattened by compression, but cannot be flattened to the same degree as polished objects.
[0061] The other of the two surfaces 10A and 10B may be a surface in which the anisotropic filler 12 is embedded inside the polymer matrix 12. The oriented molded body manufactured by the above-mentioned magnetic field orientation manufacturing method has an outermost surface that is a skin layer in which the filling ratio of the anisotropic filler is lower than other parts and typically does not contain anisotropic filler. Therefore, for example, by making the outermost surface of the oriented molded body the other of the two surfaces 10A and 10B of the thermal conductive sheet 10, the other of the two surfaces 10A and 10B can be a surface in which the anisotropic filler 12 is embedded inside the polymer matrix 12. The surface in which the anisotropic filler 12 is embedded inside the polymer matrix 12 becomes an adhesive surface. The adhesive surface can be attached to a contact object such as a heat sink or a heat generating object to fix the contact object.
[0062] [Second embodiment] Next, a thermally conductive sheet according to a second embodiment of the present invention will be described with reference to FIG. In the first embodiment, the thermally conductive sheet 10 contains a non-anisotropic filler 16 as a filler in addition to the anisotropic filler 12, but the thermally conductive sheet 20 of this embodiment does not contain the non-anisotropic filler 16, as shown in Fig. 2. That is, in the thermally conductive sheet of the second embodiment, for example, only carbon fiber may be used as a filler. The other configurations of the thermally conductive sheet 20 of the second embodiment are similar to those of the thermally conductive sheet 10 of the first embodiment described above, except that no non-anisotropic filler is contained, and therefore a description thereof will be omitted.
[0063] In this embodiment, as in the first embodiment, the anisotropic filler 12 is exposed on at least one of the surfaces 20A, 20B of the thermally conductive sheet 20, and the same effects as in the first embodiment can be obtained.
[0064] In this embodiment, as in the first embodiment, at least one surface has the anisotropic filler 12 exposed, and the arithmetic mean curvature of the peaks (Spc) is 18,000 (1 / mm) or less, thereby improving the thermal conductivity in the thickness direction. EXAMPLES
[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0066] In this example, the physical properties of the thermally conductive sheet were evaluated by the following methods. [Arithmetic mean curvature of the peak (Spc), arithmetic mean height (Sa), and developed area ratio of the interface (Sdr)] Surface property analysis was performed using a laser microscope (Keyence Corporation, VK-X150) in accordance with ISO25178. Specifically, the surface profile of a two-dimensional area of 1000 μm × 1000 μm was measured by a laser method at a lens magnification of 10 times. The average value of three measurements on the same sample was adopted as the arithmetic mean curve Spc of the peaks. Similarly, the arithmetic mean height (Sa) and the developed area ratio of the interface (Sdr) were measured at three locations on the same sample, and the average values were taken as the arithmetic mean height (Sa) and the developed area ratio of the interface (Sdr), respectively.
[0067] [Thermal resistance value] The thermal resistance value was measured using a thermal resistance measuring device as shown in FIG. 3 by the method described below. Specifically, for each sample, a test piece S with a size of 30 mm×30 mm was prepared for this test. Then, each test piece S was attached onto a copper block 22 with a measurement surface of 25.4 mm×25.4 mm and a side surface covered with a heat insulating material 21, and sandwiched between upper copper blocks 23. A load was applied by a load cell 26, and the thickness was set to 90% of the original thickness. Here, the lower copper block 22 was in contact with a heater 24. The upper copper block 23 was also covered with a heat insulating material 21 and connected to a heat sink 25 equipped with a fan. Next, the heater 24 was made to generate heat with a heat generation amount of 25 W, and 10 minutes after the temperature reached a substantially steady state, the temperature (θ j0 ), the temperature of the lower copper block 22 (θ j1 ) and the heat generation amount (Q) of the heater were measured, and the thermal resistance value of each sample was calculated using the following formula (1). Thermal resistance=(θ j1 -θ j0 ) / Q... Equation (1) In formula (1), θ j1 is the temperature of the lower copper block 22, θ j0 is the temperature of the upper copper block 23, and Q is the amount of heat generated.
[0068] [Type E hardness as specified by JIS K6253] Type E hardness was measured based on Japanese Industrial Standard JIS K 6253. Specifically, the oriented molded article produced in each example was measured using a type E durometer.
[0069] [Orientation rate] The cross section of the produced thermal conductive sheet was observed under an electron microscope, 100 anisotropic fillers (carbon fibers) were extracted, and the number of anisotropic fillers oriented in the thickness direction of the sheet was calculated among the 100. Those with 61 or more (61%) oriented were marked with a good mark, and those with less than 60 (60%) oriented were marked with an bad mark. Carbon fibers were determined to be oriented when their major axis directions were within a range of 20° from the thickness direction of the thermal conductive sheet.
[0070] [Example 1] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total 100 parts by mass, volume filling rate 36 volume%) as a polymer matrix (polymer composition), 150 parts by mass (volume filling rate 30 volume%) of carbon fiber (graphitized carbon fiber with average fiber length 100 μm, aspect ratio 10, and thermal conductivity 500 W / m K) as an anisotropic filler, and 200 parts by mass (volume filling rate 18 volume%) of alumina powder (spherical, average particle size 3 μm, aspect ratio 1.0) and 100 parts by mass (volume filling rate 13 volume%) of aluminum powder (irregular shape, average particle size 3 μm) as non-anisotropic fillers. Next, the above mixed composition was injected into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and a magnetic field of 8 T was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, resulting in a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets having a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0071] Next, both surfaces of the sheet-like molded product were reciprocally polished 50 times with coarse abrasive paper A (grain size #320) having an average abrasive grain size (D50) of 60 μm to obtain a thermally conductive sheet.
[0072] [Example 2] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the abrasive paper A was changed to abrasive paper B (grain size #4000) with finer abrasive grains and an average grain size (D50) of 3 μm, and the number of times of abrasion was changed to 15 back and forth strokes.
[0073] [Example 3] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the abrasive paper A was changed to abrasive paper C (grain size #15000) with finer abrasive grains and an average grain size (D50) of 0.3 μm, and the number of times of abrasion was changed to three back and forth passes.
[0074] [Example 4] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the polishing was changed from 50 back and forth strokes with abrasive paper A to 30 back and forth strokes with abrasive paper A, followed by 10 back and forth strokes with abrasive paper B, and then 10 back and forth strokes with abrasive paper C.
[0075] [Comparative Example 1] A thermally conductive sheet was obtained in the same manner as in Example 1, except that the sheet-like molded body was not polished.
[0076] [Example 5] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total 100 parts by mass, volume filling rate 32% by volume) as a polymer matrix (polymer composition), 150 parts by mass (volume filling rate 26% by volume) of carbon fiber (graphitized carbon fiber with average fiber length 100 μm, aspect ratio 10, and thermal conductivity 500 W / m K) as an anisotropic filler, and 475 parts by mass (volume filling rate 41% by volume) of alumina powder (spherical, average particle size 3 μm, aspect ratio 1.0) as a non-anisotropic filler. Next, the above mixed composition was injected into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and a magnetic field of 8 T was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, resulting in a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets having a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0077] Next, both surfaces of the sheet-like molded product were polished back and forth 30 times with abrasive paper A having coarse abrasive grains to obtain a thermally conductive sheet.
[0078] [Example 6] A thermally conductive sheet was obtained in the same manner as in Example 5, except that the abrasive paper A was changed to abrasive paper B having finer abrasive grains and the number of times of abrasion was changed to 15 back and forth. [Example 7] A thermally conductive sheet was obtained in the same manner as in Example 5, except that the abrasive paper A was changed to abrasive paper C having finer abrasive grains and the number of times of abrasion was changed to five back and forth.
[0079] [Example 8] A thermally conductive sheet was obtained in the same manner as in Example 5, except that the polishing was changed from 50 back and forth strokes with abrasive paper A to 30 back and forth strokes with abrasive paper A, followed by 10 back and forth strokes with abrasive paper B, and then 10 back and forth strokes with abrasive paper C.
[0080] [Comparative Example 2] A thermally conductive sheet was obtained in the same manner as in Example 5, except that the sheet-like molded body was not polished.
[0081] The sheet-like molded article or thermally conductive sheet produced in each example was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 1 below.
[0082] [Table 1]
[0083] [Example 9] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total of 100 parts by mass, volume filling rate of 36 volume%) as a polymer matrix (polymer composition), 140 parts by mass (volume filling rate of 28 volume%) of carbon fiber (graphitized carbon fiber having an average fiber length of 100 μm, an aspect ratio of 10, and a thermal conductivity of 500 W / m K) as an anisotropic filler, 5 parts by mass (volume filling rate of 1 volume%) of graphite (flake graphite powder having an average particle size of 130 μm, an aspect ratio of 10, and a thermal conductivity of 550 W / m K), and 250 parts by mass (volume filling rate of 34 volume%) of aluminum powder (irregular shape, average particle size of 3 μm) as a non-anisotropic filler. Next, the above mixed composition was injected into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and a magnetic field of 8 T was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, resulting in a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets having a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0084] Next, both surfaces of the sheet-like molded product were reciprocally polished 50 times with coarse abrasive paper A (grain size #320) having an average abrasive grain size (D50) of 60 μm to obtain a thermally conductive sheet.
[0085] [Example 10] A thermally conductive sheet was obtained in the same manner as in Example 9, except that the abrasive paper A was changed to abrasive paper B (grain size #4000) with finer abrasive grains and an average grain size (D50) of 3 μm, and the number of times of abrasion was changed to 15 back and forth strokes.
[0086] [Example 11] A thermally conductive sheet was obtained in the same manner as in Example 9, except that the abrasive paper A was changed to abrasive paper C (grain size #15000) with finer abrasive grains and an average grain size (D50) of 0.3 μm, and the number of times of abrasion was changed to three back and forth passes.
[0087] [Example 12] A thermally conductive sheet was obtained in the same manner as in Example 9, except that the polishing was changed from 50 back and forth strokes with abrasive paper A to 30 back and forth strokes with abrasive paper A, followed by 10 back and forth strokes with abrasive paper B, and then 10 back and forth strokes with abrasive paper C.
[0088] [Comparative Example 3] A thermally conductive sheet was obtained in the same manner as in Example 9, except that the sheet-like molded body was not polished.
[0089] [Example 13] A mixed composition was obtained by mixing an alkenyl group-containing organopolysiloxane and a hydrogenorganopolysiloxane (total 100 parts by mass, volume filling rate 36% by volume) as a polymer matrix (polymer composition), 150 parts by mass (volume filling rate 30% by volume) of carbon fiber (graphitized carbon fiber with an average fiber length of 100 μm, aspect ratio of 10, and thermal conductivity of 500 W / m K) as an anisotropic filler, and 250 parts by mass (volume filling rate 33% by volume) of aluminum powder (irregular shape, average particle size 3 μm) as a non-anisotropic filler. Next, the above mixed composition was injected into a mold set to a thickness sufficiently greater than that of the thermally conductive sheet, and a magnetic field of 8 T was applied in the thickness direction to orient the carbon fibers in the thickness direction. The matrix was then hardened by heating at 80°C for 60 minutes, resulting in a block-shaped oriented molded body. Next, the block-shaped oriented molded product was sliced into sheets having a thickness of 1 mm using a shear blade, thereby obtaining sheet-shaped molded products with exposed carbon fibers.
[0090] Next, both surfaces of the sheet-like molded product were polished back and forth 30 times with abrasive paper A having coarse abrasive grains to obtain a thermally conductive sheet.
[0091] [Example 14] A thermally conductive sheet was obtained in the same manner as in Example 13, except that the abrasive paper A was changed to abrasive paper B having finer abrasive grains and the number of times of abrasion was changed to 15 back and forth. [Example 15] A thermally conductive sheet was obtained in the same manner as in Example 13, except that the abrasive paper A was changed to abrasive paper C having finer abrasive grains and the number of times of abrasion was changed to five back and forth.
[0092] [Example 16] A thermally conductive sheet was obtained in the same manner as in Example 13, except that the polishing was changed from 50 back and forth strokes with abrasive paper A to 30 back and forth strokes with abrasive paper A, followed by 10 back and forth strokes with abrasive paper B, and then 10 back and forth strokes with abrasive paper C.
[0093] [Comparative Example 4] A thermally conductive sheet was obtained in the same manner as in Example 13, except that the sheet-like molded body was not polished.
[0094] The sheet-like molded product or thermally conductive sheet produced in each example was subjected to the above-mentioned measurements and evaluations. The results are shown in Table 2 below.
[0095] [Table 2]
[0096] As is clear from the results of the above examples, in the thermally conductive sheet, the anisotropic filler is exposed and the arithmetic mean curve (Spc) of the peaks is 18000 (1 / mm) or less, so that the desired thermal resistance value and thermal conductivity can be obtained and the thermal conductivity in the thickness direction can be improved. On the other hand, in the comparative example, the desired thermal resistance value and thermal conductivity could not be obtained and the thermal conductivity in the thickness direction could not be sufficiently improved. [Explanation of symbols]
[0097] 10, 20 Thermally conductive sheet 12 Anisotropic filling materials 14 Polymer matrix 21 Insulation 22 Lower Copper Block 23 Upper copper block 24 Heater 25 Heat sink 26 Load Cell S test piece θ j0 Temperature of the upper copper block θ j1 Temperature of the lower copper block
Claims
1. A thermally conductive sheet containing an anisotropic filler in a polymer matrix, at least one of whose surfaces has the anisotropic filler exposed and an arithmetic mean peak curvature (Spc) of 6517 (1 / mm) or less.
2. 2. The thermally conductive sheet according to claim 1, wherein the anisotropic filler is oriented in the thickness direction of the thermally conductive sheet.
3. The thermally conductive sheet according to claim 1 or 2, wherein the at least one surface has an arithmetic mean height (Sa) of 20 μm or less.
4. The thermally conductive sheet according to any one of claims 1 to 3, wherein the surface of the thermally conductive sheet has an interface developed area ratio (Sdr) of 70 or less.
5. The thermally conductive sheet according to any one of claims 1 to 4, wherein the anisotropic thermally conductive filler is at least one of a fibrous filler and a scaly filler.
6. The thermally conductive sheet according to any one of claims 1 to 5, having a thickness of 0.1 to 5.0 mm.
7. The thermally conductive sheet according to claim 6, which has a thickness of 0.1 to 0.3 mm.
8. The thermally conductive sheet according to any one of claims 1 to 7, wherein the arithmetic mean curve (Spc) of the peaks is 1000 (1 / mm) or more.
Citation Information
Patent Citations
Thermally conductive molded article and its manufacturing method
JP2007326976A
Heat transfer sheet
JP2008251747A
Thermally conductive resin molded product
JP2018014534A
Electromagnetic wave absorption thermal conductive sheet, method of manufacturing the same, and semiconductor device
JP2018056315A
Heat conductive sheet
WO2017179318A1